Avaliação dos marcadores do estresse oxidativo em indivíduos suplementados com ferro e ácido ascórbico - Colpo, Elisângela (2007)
Iron is an essential nutrient for cellular activities including oxygen transport, electron transfer, and gene regulation. However, iron is potentially toxic via its redox reactions which generate reactive oxygen species (ROS). Oxidative damage to biomolecules can be modulated by antioxidants such as ascorbic acid (AA). However, it is well known that in the presence of redox-active iron, AA can act as a pro-oxidant in vitro and contribute to the formation of hydroxyl radicals. Based on the possible pro-oxidant interaction of iron and AA, we evaluated the manifestations of supplementation of iron associated with the ascorbic acid. The study was delineated by nine non-smoking male healthy volunteers, aged between 20 and 31 years. The volunteers were supplemented with a single dose containing 2g of AA (first group), 150mg of iron (second group) and 2g of AA plus 150mg of iron (third group). The 9 volunteers were submitted the all the treatments, which were alternate every 15 days. The volunteers were submitted to blood collections before the supplementation and 2, 5 and 24 hours after the supplementation. They were evaluated the levels of iron and ferritin, the activity of the antioxidants enzymes catalase (CAT), gluthatione peroxidase (GPx), superoxide dismutase (SOD), the level non-enzymatic antioxidants: AA, non-protein-SH, as well as markers of the oxidative stress Thiobarbituric acid reactive substances (TBARS), diclorofluorescein oxidation and delta-amino levulinate dehydratase (ALA-D) activity. The results showed that plasma AA levels were increased at 2, 5 and 24 hours after AA or AA plus iron ingestion. Plasmatic iron level was increased at 2 hours after iron ingestion and 2, 5 hours in the group AA plus iron. The erythrocytes TBARS levels decreased at 5 hours after AA and 5, 24 hours after AA plus iron ingestion. The erythrocytes CAT levels caused a significant increase 5 hours after supplementation with AA plus iron. The other results showed no significant different in the determinations. Thus, the present study does not support the hypothesis that the combination of high plasma oncentrations of AA and iron, or iron alone, causes oxidative damage in vivo. However, further studies are required to determine if iron and AA interactions could have a pro-oxidant effect in vivo.